The Nature of Humans as Social Creatures in the Qur'an - Reva Pancarani; Didik Himmawan; Shefilla Agustiana; Chandra Novan (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
The title of this article is The Nature of Humans as Social Creatures, that is, humans as the most perfect creatures that Allah created should be able to know why and what the essence of us was created and what we must do as servants of Allah. Allah created humans with the aim of being a caliph on earth with the creation of humans who In the form of reason, this is what differentiates humans from other creatures with special features so that humans should be able to think, have faith and piety, carry out Allah's commands and avoid His prohibitions. Humans are the most perfect creation of Allah SWT. He is a creature who has various abilities, especially the ability to communicate with other humans. Humans are said to be social creatures, also because in humans there is an urge and need to relate (interact) with other people, humans will not be able to live as humans if they do not live among humans. As social creatures, humans have feelings of empathy, sympathy, tolerance, loyal friends and help each other towards other humans. With this ability, humans are said to be social creatures. Man himself is said in the Al-Qur'an to be Al-Nas, Al-Insan, and Al-Basyar. Al-Nas is a social creature, Al-Insan is a rational human being, Al-Basyar is a biological creature who needs primary impulses. The verses of the Al-Qur'an that relate to relationships between humans as social creatures are Al-Isra verse 7, Al-Hujurat verse 11, Al-Baqarah verse 213.